ANALISIS TEKNIS PENANGKAPAN DAN KOMPOSISI HASIL TANGKAPAN MENGGUNAKAN PUKAT HELA (Trawl) DI PESISIR UTARA TARAKAN - Nano Saputra; Gazali Salim; - Yulma (Jurnal Harpodon Borneo, 2016)
The aim of research is analyze of technical arrest and composition of the catch of fishermen using trawl hela in waters the northern coast of Tarakan.  This research used a descriptive exploratory. Retrieving data using purposive sampling station by 10%. The results research of the technical fisheries trawl of hela in Waters Juata ; Ship category is 47% ; while the smallest 12%.  Cargo capacity (GT) most dominating 3 GT 47%, while the smallest 6% : fishermen in the value of the engine unit 2 of 59%. Duration setting, towing, and hauling every fisherman, but the most dominating of any duration : set a duration of 20 minutes as much as 47% : 5 hours towing as much as 53% ; Transporting a duration of 30 minutes, as much as 41%. The results of the study the total number of catches that all fishermen ; Main catch capturing 91%, while the catch by capturing 6%; Dispose of catches at 3% ; The main catches are playing the highest catch of fishermen as much as 430 kg ; Catches up with the catch at the dominance is Penaeus esculentus by 30% ; Discard catch was dominated is Prapenaepsis sculptilis by 30%.Keywords: trawl hela; technical arrest; catch composition; Tarakan